Pengaruh Likuiditas, Solvabilitas dan Nilai Pasar Terhadap Return Saham - Dede Hertina; Mohamad Bayu Herdiawan Hidayat (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2019)
The purpose of this study was to determine the information, solvability, and value of shares of the Agricultural Sector Companies listed on the Indonesia Stock Exchange for the 2012-2016 period. The method used in this research is descriptive and verification method with a quantitative approach. Research Results The company with the highest liquidity in 2012 was PT Bumi Teknokultura Unggul Tbk with liquidity of 6747.74, and the company with the lowest liquidity in 2013 was PT Bumi Teknokultura Unggul Tbk with liquidity of 14.33. The highest solvency value is PT. Central Proteinaprima Tbk amounted to 64.05, while the lowest solvency value in 2015 was owned by PT Inti Agri Resources Tbk at 0.04. The highest Market Value in 2012 was PT. Central Proteinaprima Tbk amounted to 38.72, while the lowest average market value in 2016 was PT Gozco Plantation Tbk of 0.19. The highest Stock Return Value in 2014 was PT. Central Proteinaprima Tbk at 1.06, while the lowest stock return value in 2015 was owned by PT Eagle High Plantations Tbk at -0.66.